Guest Editorial: Governance and Ethics: An Indispensable Relationship - Armstrong , Anona (Journal of Law and Governance, 2008)
One of the fascinating questions of our time is why, when so much effort has gone into implementing corporate governance guidelines and raising the awareness of business ethics, stories of unethical conduct and poor governance continue to emerge on the front pages in our newspapers. Around the world financial scandals continue to occur and each time seekers of an antidote to the latest disaster call for more governance. This was evident after the 1987 securities market collapses when the Cadbury Committee and the OECD (Cadbury 1992; OECD 1999) were among many organisations which were to introduce governance regulations and guidelines over the next decade, and it is again prominent today.